Programming high-intensity training in handball - Buchheit, M. (ASPETAR Sports Medicine Journal, 2014)
Handball is called a `transition game` because players frequently switch between defensive and offensive play, and the game action is characterised by frequent intermittent running and sprinting. Technical skills, anthropometric characteristics and high levels of strength, muscle power and throwing velocity are the most important factors for gaining a clear advantage for successful participation at elite levels of handball leagues1,2. However, the importance of aerobic capacity should not be underestimated.